Diversite Floristique Et Structure Des Fragments Forestiers Du Sud-Ouest Du Parc National De La Comoe Apres Les Conflits Des Annees 2000 En Côte d’Ivoire - Seydou, Yéo Zahana; Yao Charles, Sangne; Sabas, Barima Yao Sadaiou; Issouf, Bamba; Apollinaire, Kouakou Kouassi (European Scientific Journal, ESJ, 2017)
Côte d’Ivoire, like many countries in Africa, has experienced a decade of crises that has not been without consequences for the natural formations in general and protected areas in particular. The objective of this study is to evaluate the floristic diversity and structure of forest fragments Southwest of National Park of Comoé after conflicts. The sampling methodology was to inventory all taxa along 500 meters long and a width of 10 m (5 m either side of the main line) installed in each forest fragment. In addition to the inventory of taxa, we measured the circumference of all trees at least 30 cm with their corresponding pitch. A total of 12 transects were sampled in 12 fragments of forest. Following these inventories, 256 plant species have been identified, the most abundant belong to the families of Rubiaceae and Fabaceae. 23 species have been recognized as having a special status, including Salacia miegei N. Halle and Uvaria tortilis A. Chev. Ex Hutch. & Dalziel are endemic to the Côte d’Ivoire. Nine (9) others species have been identified as species of high commercial value for the quality of their wood. The forest formations are very dense with more than 550 trees / ha. It appears that the fragments contain few large trees. Despite the successive crises, it appears that forest fragments Southwest National Park Comoé still have good potential floristic.